Association between uptake of selected vaccines and undernutrition among Nigerian children - Ryoko Sato (Taylor & Francis Group, 2021)
Introduction: Vaccination coverage among undernourished children often associated with higher risk of contracting infectious diseases due to lowered immunity is a critical public health concern. The vaccination coverage is low and the child mortality rate is high in Nigeria. This study investigates the association between selected vaccines uptake and undernutrition among Nigerian children. Methods: The 2018 Nigeria Demographic and Health Survey dataset was used for this study. Children aged 0-36 months were included in the study. Stunting and wasting were the main outcome variables to define undernutrition outcomes. The effect of BCG, first dose of DPT/Pentavalent (DPT/Penta1), third dose of DPT/Pentavalent (DPT/Penta3) and measles vaccines on nutrition outcomes were individually examined using logistic regression at 5% significance level. Results: Among 6,928 children aged 0 to 36 months old, 34.4% were stunted and 8.7% were wasted, while the vaccination rate was 70.0% (BCG), 65.0% (DPT/Penta1), 48.2% (DPT/Penta1), and 43.6% (measles). Vaccination uptake was consistently associated with less likelihood of stunting, while it was not associated with wasting. We also found that some vaccination uptake was negatively associated with stunting particularly among older children. Discussions/Conclusion: The finding that vaccination is associated with less likelihood of stunting implies that the vaccination can be important to enhance the long-term nutrition outcomes. Targeting children with disadvantageous sociodemographic characteristics for vaccination can further enhance the overall nutrition outcomes among them.